WHAT IS PHILOLOGY? PHILOLOGY AND ITS UTILISATION IN THE STUDY OF LINGUISTIC VARIATION AND CHANGE - Palola, Elina (Eesti Rakenduslingvistika Ühingu aastaraamat, 2020)
In this paper, I study the essence of philology from the perspective of the study of linguistic variation and change in old texts by examining: What is philology? What are philological research methods? What makes a study philological – does it suffice that it focuses on an old text? Has philology been defined more based on the research subjects than based on the methods? I will showcase the status of philology and its significance as a research trend that combines several disciplines. This paper focuses on the traditions of Finnish philology, but it also offers some insight into the essence of philology from a general perspective of the study of languages as the background. The goal is to offer an idea of what the philological research approach has to offer modern research of old texts. Furthermore, I will present a method that I have developed and its benefits in the study of variation and change of old texts. I will also present an analysis of the Finnish noun varve ‘pasture’, which Mikael Agricola used in the first handbook for mass in Finnish. I consider philology to be a sub-discipline of linguistics. It studies and compares old texts with text-critical methods based on their cultural and historical background.